2005
DOI: 10.1037/0893-164x.19.3.263
|View full text |Cite
|
Sign up to set email alerts
|

The effects of alcohol on cigarette craving in heavy smokers and tobacco chippers.

Abstract: The authors examined the effects of alcohol consumption on cigarette craving in heavy smokers and tobacco chippers (n = 138) who were instructed not to smoke for 12 hr. Participants were exposed to both smoking cues (a lit cigarette) and control cues. Half received a moderate dose of alcohol, adjusted for gender, and half received a placebo. Results indicated that alcohol consumption produced an increase in urge-to-smoke ratings before smoking cue exposure. Moreover, during cue exposure, alcohol consumption pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
105
2
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(125 citation statements)
references
References 50 publications
17
105
2
1
Order By: Relevance
“…This work expands on initial expectancy findings we reported elsewhere (Sayette, Martin, Wertz, Perrott, & Peters, 2005;Sayette, Martin, Wertz, Shiffman, & Perrott, 2001). In each of these prior studies, smoking expectancy data were reported in the context of a multidimensional assessment.…”
Section: Introductionmentioning
confidence: 55%
See 3 more Smart Citations
“…This work expands on initial expectancy findings we reported elsewhere (Sayette, Martin, Wertz, Perrott, & Peters, 2005;Sayette, Martin, Wertz, Shiffman, & Perrott, 2001). In each of these prior studies, smoking expectancy data were reported in the context of a multidimensional assessment.…”
Section: Introductionmentioning
confidence: 55%
“…Alternatively, the effects of alcohol on smokers' expectancies may be mediated by their urge to smoke, such that smoking expectancies shift as alcohol consumption increases smokers' smoking urge. Evidence indicates that alcohol consumption increases subjective smoking urge (Burton & Tiffany, 1997;King & Epstein, 2005;Sayette et al, 2005), but it is unclear whether alcohol consumption has an additive effect on expectancies that is independent of urge. A primary aim of Experiment 2 was to evaluate these alternative perspectives regarding the combined influence of smoking abstinence and alcohol consumption on smoking-related outcome expectancies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifi cally, several theories have been put forth attempting to explain the concurrent heavy use of cigarettes and alcohol (Durazzo et al, 2007), including conditioned cue reactivity leading to cravings for both substances (Drobes, 2002). Several studies have examined this notion by testing self-reported cravings after exposure to alcohol and smoking cues (Epstein et al, 2007;Erblich et al, 2009;King et al, 2009;Sayette et al, 2005), and it was found that moderate oral doses of alcohol increase nicotine craving in tobacco "chippers" or light smokers. To our knowledge, only one study used a functional magnetic resonance imaging (fMRI) approach to examine brain responses to an alcohol-induced smoking urge in heavy drinking nondaily smokers, where the ventral striatum demonstrated increased activation after alcohol intake (King et al, 2010).…”
mentioning
confidence: 99%